Effective online COVID-19 messages? A thematic analysis of major senior living community websites in the United States. Issue 4 (2nd October 2021) - Pan, Po-Lin; King, Shelby
Abstract: Due to seniors being at high risk of severe COVID-19, senior living communities became most impacted settings from COVID-19. This study investigated how senior living communities managed COVID-19 by looking at situational factors in their responses to COVID-19 on their websites. The study found that COVID-19 information had the least presence on the websites. However, most communities still exhibited their efforts to practice COVID-19 preventions. Many websites provided detailed vaccination information to encourage people to be vaccinated for new normal, while others illustrated the impact of social isolation on mental and physical health of their residents with health recommendations.